Current Concepts on Pathogenic Mechanisms and Histopathology in Cutaneous Lupus Erythematosus - Fetter, Tanja; Braegelmann, Christine; de Vos, Luka; Wenzel, Joerg (Frontiers in Medicine, 2022)
Cutaneous lupus erythematosus (CLE) is an interferon (IFN)-driven autoimmune disease that may be limited to the skin or can be associated with systemic lupus erythematosus (SLE). CLE occurs in several morphologic subtypes ranging from isolated, disc-shaped plaques to disseminated skin lesions. The typical histopathologic pattern of skin lesions is named interface dermatitis and characterized by a lymphocytic infiltrate and necroptotic keratinocytes at the dermo-epidermal junction. Other histopathologic patterns primarily involve the dermis or subcutis, depending on the subtype. One critical mechanism in CLE is the chronic reactivation of innate and adaptive immune pathways. An important step in this process is the recognition of endogenous nucleic acids released from dying cells by various pattern recognition receptors (PRRs), including Toll-like receptors (TLRs) and other cytosolic receptors. Crucial cells in CLE pathogenesis comprise plasmacytoid dendritic cells (pDCs) as major producers of type I IFN, T cells exerting cytotoxic effects, and B cells, previously believed to contribute via secretion of autoantibodies. However, B cells are increasingly considered to have additional functions, supported by studies finding them to occur in highest numbers in chronic discoid lupus erythematosus (CDLE), a subtype in which autoantibodies are often absent. More precise knowledge of how CLE subtypes differ pathophysiologically may allow a tailored pharmacotherapy in the future, taking into account the specific molecular signature in relation to the morphologic subtype.